Killing me softly: myth in pharmaceutical advertising. Issue 7480 (16th December 2004) - Scott, Tim; Stanford, Neil; Thompson, David R
Abstract : In studies of how drug advertising influences doctors' behaviour, little attention is given to visual and linguistic imagery. The authors argue that myth is often deployed in drug adverts to depict exaggerated therapeutic efficacy and that doctors should be aware of this